2014
DOI: 10.1007/s10459-013-9483-3
|View full text |Cite
|
Sign up to set email alerts
|

Learning with interactive computer graphics in the undergraduate neuroscience classroom

Abstract: Instruction of neuroanatomy depends on graphical representation and extended self-study. As a consequence, computer-based learning environments that incorporate interactive graphics should facilitate instruction in this area. The present study evaluated such a system in the undergraduate neuroscience classroom. The system used the method of adaptive exploration, in which exploration in a high fidelity graphical environment is integrated with immediate testing and feedback in repeated cycles of learning. The re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 32 publications
0
9
0
1
Order By: Relevance
“…For instance, computer animations have been successfully used by medical educators for teaching anatomy and histology (Brisbourne et al, ), physical examination (Houck et al, ) and various surgical techniques (Mehrabi et al, ; Henderson and Ali, ), however, these have not always proven to be effective (discussed in Ruiz et al, ). Various other online pedagogical tools, which were investigated in the current survey included 2D and 3D radiological models/images, videos of lectures and surgical procedures, snapshots of plastinated models, atlas images, and podcasts have been reported to improve learning outcomes (Lozanoff et al, ; Estevez et al, ; Chariker et al, , ; Pani et al, ; Bacro et al, ; Pani et al, ; Drapkin et al, ; Biesalski, ). In an era when the resources required for traditional anatomy teaching have become limited, CAL and online web‐resources have huge potential to effectively support teaching and learning, however, their design and implementation must be carefully crafted.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, computer animations have been successfully used by medical educators for teaching anatomy and histology (Brisbourne et al, ), physical examination (Houck et al, ) and various surgical techniques (Mehrabi et al, ; Henderson and Ali, ), however, these have not always proven to be effective (discussed in Ruiz et al, ). Various other online pedagogical tools, which were investigated in the current survey included 2D and 3D radiological models/images, videos of lectures and surgical procedures, snapshots of plastinated models, atlas images, and podcasts have been reported to improve learning outcomes (Lozanoff et al, ; Estevez et al, ; Chariker et al, , ; Pani et al, ; Bacro et al, ; Pani et al, ; Drapkin et al, ; Biesalski, ). In an era when the resources required for traditional anatomy teaching have become limited, CAL and online web‐resources have huge potential to effectively support teaching and learning, however, their design and implementation must be carefully crafted.…”
Section: Discussionmentioning
confidence: 99%
“…More globally than neuroanatomy, it has also been suggested that computerized models may be more effective than cadaveric tissues for teaching anatomy overall (Robb, ; Sugand et al, ). One of the reasons why researchers believe that computer generated brain models are superior to physical models is because they can be rotated, changed into sectional anatomy and incorporate into transparent layers of anatomy (Pani et al, ). These arguments could be used against implementation of dissection protocols such as the one proposed here.…”
Section: Discussionmentioning
confidence: 99%
“…Many recent advances in neuroanatomy teaching tools include computer-generated models (Gould et al, 2008;Adams and Wilson, 2011;Chariker et al, 2011Chariker et al, , 2012Pani et al, 2013Pani et al, , 2014Drapkin et al, 2015). Although there is much variation between computer generated models and 3D computer graphics, it has been suggested that computerized models will improve in anatomic accuracy (Toga et al, 2006) and may become even more utilized in teaching undergraduate neuroanatomy.…”
Section: Figurementioning
confidence: 99%
“…Although beyond the scope of this manuscript, a comprehensive review of the technological underpinnings of 3-D displays was presented by Geng in 2013. 22 Within medical education literature, 3-D display technologies have been implemented and studied for a wide range of anatomical structures, particularly where anatomy is spatially more difficult to understand, 24 including the inner ear, 25 carpal bones, 26 heart, 27 liver, 28 brain, [29][30][31][32] and numerous other structures. Meta-analyses and review articles on the subject have found that 3-D visualisations are generally beneficial for student performance and are viewed positively by students.…”
mentioning
confidence: 99%